Simple Interactions: A randomized controlled trial of relational training for adults who work with young people across settings. Issue 2 (3rd April 2022) - Akiva, Thomas; White, Annie M.; Colvin, Sharon; DeMand, Alex; Page, Lindsay C.
Abstract: Research across multiple fields finds that adult-youth relationships are key influencers of development; however, professional learning about relational practice is limited. This suggests the need for targeted, efficient ways to help adults improve relational practice. We present a randomized controlled trial of Simple Interactions, a strength-based professional development approach during which participants reflect on short videos of themselves interacting with young people using a dialogic protocol. Participating staff expressed high satisfaction with Simple Interactions, rating an average of 4.56 out of 5.00 on a 7-item composite measure. We saw an experimental effect for belief change, with treatment group staff after the workshops rating relational practice as more important than control group staff. We did not see an experimental effect for relational practice, perhaps due to substantial challenges around workshop attendance. The findings are promising for the innovation and suggest more engagement may be necessary to see change in practice.